Garden as an environmental intervention in healing process of hospitalised children - Said, Ismail (2003)
Hospitalisation often erodes the feelings of toddlers and young children causing regressive behaviours and stress, which result in reduced cognitive performance, helplessness, restlessness, crying, anxiety, and elevated blood pressure. Having the ill children experiencing a garden setting, either in a passive or an active mode, can arouse their senses that nurture their inductive and deductive, motor-impulses development and reflective thinking capabilities. These interactions have resulted in psychological peacefulness and adjustment by the children including being more cooperative toward medication, less crying, more active and cheerful, and more obedient to caregivers. The behavioural responses are considered positive clinical outcomes that foster recovery rate of the hospitalised children. Hence, the garden can be viewed as an environmental intervention in enhancing the healing process of ill children in hospital environment.